The Relationship between Personal Hygiene and Household Insecticide Use with Parkinsonism on Farmers at Juhar Ginting Sadanioga - Andin Rizqika Aliunputri Andin; Taufik Ashar; Rahayu Lubis (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Parkinson's disease attacked millions of people in the world, or about 1% of the world's total population. The cause of Parkinson's disease is unclear, but one of them is an environmental factor. Environmental factors that lead to this disease is pesticide exposure. The purpose of this research to analyze the relationship of personal hygiene and the household insecticide use with Parkinsonism in farmers. This research was an observational analytic with cross-sectional design. The sample amounted to 60 people and taken by simple random sampling technique. The data obtained through interviews and observations using a questionnaire. This study resulted that 53.3% of farmers had Parkinsonism. As many as 21.7% of farmers had poor personal hygiene, and 63.3% of farmers were household insecticide use. The chi-square test showed that there was a significant relationship between personal hygiene with Parkinsonism (p = 0.0001), and there was a significant relationship between household insecticide use with Parkinsonism (p = 0.001).